The Analysis of Diplomatic Relations between Turkey and Greece Until 2021 - Chaerunnisa, Salsabila Putri (Universitas Sebelas Maret, 2022)
This paper analyzes the diplomatic relations between Turkey and Greece which are constantly changing. The relationship between the two are volatile, where the relationship of cooperation and conflict occurred alternately over the years. Turkey and Greece have a dark history due to war, but in 1999 they decided to open diplomatic relations after implementing disaster diplomacy. However, the relationship between the two tends to lead to disputes over the territory of Cyprus, Aegean Sea, and Mediterranean Sea. Also land border problems due to global migration because both are neighboring countries. Although the relationship between Turkey and Greece often heat up, the two also carry out bilateral cooperation, especially in the economic field. This paper aims to analyze and explain the reasons behind the dynamics of diplomatic relations between Turkey and Greece since the opening of embassies in the two countries until now. To analyze this paper, rational choice theory and the concept of national interest are used based on a neorealism perspective.